An Evolution of Assistive Robot Control to Meet End-User Ability - Thompson, Andrew; Rizzoglio, Fabio; Neylon, Fiona A; Barsoum, Demiana R; Ammon, Lucy E; McCune, Maximus N; Miller, Lee; Argall, Brenna (Companion of the 2024 ACM/IEEE International Conference on Human-Robot Interaction. ACM/IEEE Conference on Human-Robot Interaction (2024 : Boulder, Colo.), 2024)
In this work, we present an evolution of system designs and studies that aim to facilitate the operation of high-DoF assistive robotic arms by persons with upper limb paralysis. We highlight the experimental pipeline and note developments in our efforts to design a suitable control map that can convert low variance residual body motions from neuromotor-impaired populations into 6-D velocity control signals for use in teleoperating a 7-DOF robotic arm. Notably, we provide results from variance analyses on raw IMU control signals from both neuromotor-impaired and unimpaired populations, and an analysis of the intrinsic dimensionality of map-building datasets gathered with and without movement guidance. We then present a preliminary 13-session study that vets the control map developed in light of these findings.